Stuff matters : exploring the marvelous materials that shape our man-made world - Miodownik, Mark (Houghton Mifflin Harcourt, 2014)
"Why is glass see-through? What makes elastic stretchy? Why does a paperclip bend? Why does any material look and behave the way it does? With clarity and humor, world-leading materials scientist Mark Miodownik answers all the questions you've ever had about your pens, spoons, and razor blades, while also introducing a whole world full of materials you've never even heard of: the diamond five times the size of Earth; concrete cloth that can be molded into any shape; and graphene, the thinnest, strongest, stiffest material in existence--only a single atom thick.Stuff Matters tells enthralling stories that explain the science and history of materials. From the teacup to the jet engine, the silicon chip to the paper clip, the plastic in our appliances to the elastic in our underpants, Miodownik reveals the miracles of engineering that permeate our lives. As engaging as it is incisive, Stuff Matters will make you see the materials that surround you with new eyes"--